Concept understanding ability: Error analysis of Madrasah Aliyah students in solving problems based on Kastolan stages - Gunawan, Sanie Rachma Setia; Dahlan, Jarnawi Afgani; Darhim, Darhim (Universitas Islam Raden Intan Lampung, INDONESIA, 2025)
Purpose: This study aims to analyze the types of errors made by Madrasah Aliyah (MA) students in solving problems related to concept understanding in statistics, based on Kastolan’s stages.Method: A qualitative approach using a phenomenological method was employed to deeply explore students' error patterns. Data were collected through concept understanding tests, documentation, and interviews, involving 12 grade 12 students selected by purposive sampling. The analysis followed the Miles and Huberman model.Findings: The results revealed that students with high, moderate, and low concept understanding abilities all made errors categorized into conceptual, procedural, and technical errors. Conceptual and procedural errors stemmed from limited understanding of statistical concepts such as mode, median, and mean. Technical errors were caused by lack of accuracy, insufficient exposure to varied problem types, and low student independence in learning.Significance: This study highlights the importance of reinforcing basic statistical concepts in teaching and suggests that varied and non-routine problem exercises are essential to reduce students’ errors and enhance conceptual understanding.